Wet Chemical Controllable Synthesis of Hematite Ellipsoids with Structurally Enhanced Visible Light Property - Chengliang Han; Jie Han; Qiankun Li; Jingsong Xie (The Scientific World Journal)
A facile and economic route has been presented for mass production of micro/nanostructured hematite microcrystals based on the wet chemical controllable method. The as-prepared samples were characterized using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and UV-Vis absorption spectroscopy. The results showed that the product was mesoporous α-Fe2O3 and nearly elliptical in shape. Each hematite ellipsoid was packed by many α-Fe2O3 nanoparticles. The values of vapor pressure in reaction systems played vital roles in the formation of porous hematite ellipsoids. Optical tests demonstrated that the micro/nanostructured elliptical hematite exhibited enhanced visible light property at room temperature. The formation of these porous hematite ellipsoids could be attributed to the vapor pressure induced oriented assembling of lots of α-Fe2O3 nanoparticles.